Development of ways to improve strategic financial planning in an enterprise - Iorgachova, Maria; Kovalova, Olena; Kirsanova, Viktoriia (Technology audit and production reserves, 2025)
The research object is the issue of strategic financial planning at enterprises under conditions of high uncertainty in the external economic environment. One of the most problematic aspects is the need to improve strategic financial planning in conditions of economic turbulence, as its successful implementation is a prerequisite for financial stability and effective operations. The research utilized methods of analysis and synthesis, critical analysis and generalization methods, graphical methods, an algorithmic approach, and an expert method. A set of universal practical recommendations has been developed to improve the process of strategic financial planning at enterprises by generalizing conceptual theoretical and methodological foundations. This is due to the fact that the proposed improvement directions feature a number of specific characteristics that must align with external operating conditions. They also account for the peculiarities of different development stages, enterprise-specific activities, as well as various tools and approaches to achieve the primary goal. The study identifies barriers complicating the implementation of strategic financial planning at Ukrainian enterprises, including a lack of financial resources, the complexity of planning methodologies, and the high uncertainty of the external environment. The developed pool of recommendations enables improvements in a set of key performance indicators for the functioning of business entities by integrating these recommendations into the process of strategic financial planning. Achieving a qualifying effect becomes possible through the simultaneous use of ratio analysis combined with a balanced scorecard system, forecasting, and a scenario-based approach. The proposed authorial approach represents the most suitable option for implementing strategic financial planning under modern conditions. Compared to similar known approaches, it offers advantages such as cost optimization, clarification of the qualifying impact of factors on resulting indicators, and integration of advanced methodologies. The integration of innovative tools is driven not only by technological progress but also by new market demands, changes in consumer behavior, and the globalization of business processes.